Plasminogen activating inhibitor‐1 promotes angiogenesis in cutaneous angiosarcomas. Issue 1 (2nd October 2022) - Ohuchi, Kentaro; Amagai, Ryo; Ikawa, Tetsuya; Muto, Yusuke; Roh, Yuna; Endo, Junko; Maekawa, Takeo; Kambayashi, Yumi; Asano, Yoshihide; Fujimura, Taku
Abstract: Plasminogen activating inhibitor‐1 (PAI‐1) is associated with poor clinical outcomes, and elevated levels of PAI‐1 in both tissue and serum are correlated with poor response to therapy in various cancers, including skin cancer. Cutaneous angiosarcoma (CAS) is a vascular tumor histologically characterized by detachment of endothelial cell‐derived tumor cells. Since CAS expresses multiple angiogenic growth factors and has increased expressions of angiogenic receptor tyrosine kinase transcripts including VEGFR1/2/3, angiogenesis‐promoting factors are potential drug targets in CAS. In this study, the expression of PAI‐1 was examined in 31 cases of CAS, and the immunomodulatory effects of PAI‐1 on a human CAS cell line, ISO‐HAS‐B, were evaluated. We found that, of the angiogenesis‐promoting factors, PAI‐1 was expressed in almost all cases of CAS, and PAI‐1 increased the mRNA expressions of IL‐23p19, VEGF‐C, CXCL5 and CCL20 on ISO‐HAS‐B. Moreover, PAI‐1 stimulated ISO‐HAS‐B culture supernatant promoted favourable tube networks, suggesting that these tumor‐derived factors promote the pro‐angiogenic effect on tumor development. In addition, IL‐23p19 was expressed in 61.3% of cases, whereas VEGF‐C was expressed in 41% of cases. The results of the present study suggest that PAI‐1 promotes angiogenesis that results in tumor progression in CAS.